AUDIT TATA KELOLA SISTEM INFORMASI BLACKPAINT PADA CV. BLACKPAINT PRINT SHOP PEKANBARU MENGGUNAKAN FRAMEWORK COBIT 2019 SUBDOMAIN APO14 DAN EDM04 - Sandi, Kelvin Mei; Hafiez Zahran; Megawati (Yayasan Nuraini Ibrahim Mandiri, 2025)
Information technology has an important role in supporting the continuity and efficiency of company operations. This research aims to evaluate the level of IT governance capability at CV. Blackpaint Print Shop Pekanbaru using the COBIT 2019 framework, especially in the APO14 (Managed Data) and EDM04 (Ensure Risk Optimization) subdomains. The methods used include literature study, observation, interviews, and distributing questionnaires to internal company parties. The assessment was carried out based on the Guttman scale and the Capability Level of COBIT 2019. The results showed that in the APO14 subdomain, the company had reached a capability level of up to Level 4, with the majority of activities having been carried out consistently and documented. However, the approach to innovation and continuous improvement is still not optimal. Meanwhile, in subdomain EDM04, the company shows capability up to Level 3, indicating that risk management has been implemented, but not yet supported by a quantitative and systematic approach. Recommendations are given in the form of strengthening performance measurement, risk documentation, and developing innovation in IT management. This research is expected to be a reference in making strategic decisions and improving IT governance in similar organizations.